2021
DOI: 10.1111/bjh.17321
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life maintained over time in patients with relapsed or refractory multiple myeloma treated with daratumumab in combination with bortezomib and dexamethasone: results from the phase III CASTOR trial

Abstract: In the phase III CASTOR trial, daratumumab, bortezomib and dexamethasone (D-Vd) significantly extended progression-free survival compared with bortezomib and dexamethasone (Vd) alone in patients with relapsed/refractory multiple myeloma (RRMM). Here, we present patient-reported outcomes (PROs) from the CASTOR trial. PROs were assessed using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30-item (EORTC QLQ-C30) and the EuroQol 5dimensional descriptive system qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the phase 3 CASTOR study, patients (median of 2 prior LOT; range, 1-10) treated with daratumumab, bortezomib, and dexamethasone maintained baseline levels of HRQoL throughout eight treatment cycles; thereafter, patients receiving longterm daratumumab treatment reported improvements in some PROs, including GHS, pain, and VAS scores. 36,37 In the phase 3 POLLUX study, patients (median of 1 prior LOT; range, 1-11) with RRMM treated with daratumumab, lenalidomide, and dexamethasone (D-Rd) experienced significant between-group differences from baseline in EORTC QLQ-C30 GHS, functional, and symptom scores, and EQ-5D-5L VAS scores at several time points over the course of treatment compared with patients treated with Rd alone. 38,39 Notably, the lack of negative impact of long-term therapy illustrates that the clinical benefits observed with D-Rd were not at the expense of patients' HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…In the phase 3 CASTOR study, patients (median of 2 prior LOT; range, 1-10) treated with daratumumab, bortezomib, and dexamethasone maintained baseline levels of HRQoL throughout eight treatment cycles; thereafter, patients receiving longterm daratumumab treatment reported improvements in some PROs, including GHS, pain, and VAS scores. 36,37 In the phase 3 POLLUX study, patients (median of 1 prior LOT; range, 1-11) with RRMM treated with daratumumab, lenalidomide, and dexamethasone (D-Rd) experienced significant between-group differences from baseline in EORTC QLQ-C30 GHS, functional, and symptom scores, and EQ-5D-5L VAS scores at several time points over the course of treatment compared with patients treated with Rd alone. 38,39 Notably, the lack of negative impact of long-term therapy illustrates that the clinical benefits observed with D-Rd were not at the expense of patients' HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…In the CASTOR trial, during the initial eight cycles, there were no changes in patients’ HRQOL in either of the treatment groups. However, patients receiving long-term DARA therapy reported improvements in GHS and pain following this point [ 99 ]. Furthermore, a post hoc analysis stratified by age (<65 years vs. ≥65 years) was conducted, showing that the benefits of incorporating DARA were observed regardless of age.…”
Section: The Effect Of Dara-containing Regimens On the Qol In Elderly...mentioning
confidence: 99%
“…A post hoc analysis of patient-reported health-related quality of life (HRQoL) data from the ICARIA-MM study revealed that HRQoL was maintained in patients with RRMM treated with isatuximab plus Pd versus Pd. 40 Similarly, patient-reported outcomes from the phase 3 POLLUX and CASTOR studies showed no significant change in HRQoL with the addition of daratumumab to dexamethasone plus lenalidomide 41 or bortezomib, 42 respectively, in patients with RRMM.…”
Section: Clinical Studiesmentioning
confidence: 99%